QuickStat: Empowering Statistical Understanding Through Interactive Games - Azman, Nurazmina; Mat Noor, Siti Fadzilah; Mohamed, Hazura; Alfaqiri, Abdullatif Saleh (Journal of ICT in Education, 2025)
With the rapidly growing world of technology in this era, the gaming field has driven education to engage students with new learning approaches. Statistics is a subject that requires a high level of understanding, and there are various topics, such as hypothesis testing. Hypothesis testing is a form of statistical inference and a tool that uses data from a sample to conclude a population parameter or a population probability distribution, and can be used to test whether a hypothesis, primarily a derived hypothesis, is true or false. Nevertheless, students find statistical hypothesis testing topics very difficult to understand, and previous research shows that many students in the university experience poor performance in the statistics subject. This problem is caused by an inadequate environment, a lack of interest in calculation-related subjects, and the traditional teaching method used by the faculty. Therefore, the Application of Statistical Hypothesis Testing Learning Based Gamification (QuickStat) is developed to stimulate student interest and motivation, improve comprehension, and create an interactive learning environment among Faculty of Information Science and Technology (FIST) students at Universiti Kebangsaan Malaysia (UKM) and students from different institutions that take Statistics subject. This project aims to develop and test the application of a statistical learning-based game under a hypothesis testing topic. The development of this application will apply multimedia elements such as texts, graphics, audio, videos, and animations, which will be developed using Agile methodology. Usability testing was conducted on 30 users of FTSM students, UKM, including first-year, second-year, third-year, and fourth-year students. The test results show that many users accept the QuickStat application.